2015
DOI: 10.1159/000438820
|View full text |Cite
|
Sign up to set email alerts
|

Citrate Formulation Determines Filter Lifespan during Continuous Veno-Venous Hemofiltration: A Prospective Cohort Study

Abstract: Introduction: We conducted an 8-month prospective single-center observational study in patients with acute kidney injury treated with continuous veno-venous hemofiltration (CVVH) to compare the impact of two citrate formulations on filter lifespan (FLS). Methods: Patients received CVVH at a delivered dose of 25 ml/kg/h. Multivariable linear regression was performed to assess the influence of different variables on circuit lifespan. Results: We included 59 patients, 28 received the 10/2 formulation and 31 recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Veno-venous access was obtained via a 13 F double-lumen polyurethane catheter (Joline, Swiss Confederation) inserted in the right internal jugular or a femoral vein. CVVH was delivered according to a dedicated protocol inspired by Tolwani et al [17] and presented in detail previously [6]. This included standardized order sets and initial settings for all patients.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Veno-venous access was obtained via a 13 F double-lumen polyurethane catheter (Joline, Swiss Confederation) inserted in the right internal jugular or a femoral vein. CVVH was delivered according to a dedicated protocol inspired by Tolwani et al [17] and presented in detail previously [6]. This included standardized order sets and initial settings for all patients.…”
Section: Methodsmentioning
confidence: 99%
“…Calcium chloride initially ran at 6 mL/h through a separate central venous line. Calcium infusion was titrated to maintain plasma ionized calcium levels between 1,0 and 1,2 mmol/L [6]. PC10/2 was delivered before the filter and started at a rate of 2200 mL/h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-filter iCa in this study, however, was much lower in the C14 than in the C11 group (0.40 vs. 0.52 mmol/l, p < 0.0001). Jacobs et al [11] strictly kept post-filter iCa levels between 0.2 and 0.3 mmol/l in all patients receiving RCA with either C18 or C10/2 and reported better filter survival with the higher-concentrated liquid (median 98.4 vs. 64.3 h; C18 vs. C10/2, p = 0.001).…”
mentioning
confidence: 97%
“…However, no definite answer can be provided because post-filter ionized calcium (iCa) concentrations were not reported. Indeed, keeping post-filter iCa within tight limits has been shown to ensure more optimal anticoagulation, better regulation of buffer supply, and an improved FLS [11] . Egi et al [10] found a prolonged mean FLS when a more concentrated citrate solution was used (17.1 vs. 12.2 h; C14 vs. C11).…”
mentioning
confidence: 99%